The broadcasting activity since Constitutional Amendment 08/1995: atypicality of the conduct provided for in Article 70 of Law No. 4.117/1962 and Article 183 of Law No. 9.472/1997 (Revista do Tribunal Regional Federal da 3ª Região, 2015)
In 2003, I defended my master's thesis on the subject of “Community broadcasting in the context of the Brazilian Democratic State of Law”, in which I dealt with the various aspects involving the use of the electromagnetic spectrum, especially criminal discipline, concluding that the conduct provided for in Article 70 of Law No. 4,117/1962 and Article 183 of Law No. 9,472/1997 was atypical. The topic was chosen because there is a significant number of cases of this nature in the criminal court of the Federal Court of São Paulo, surpassing cases of crimes considered more serious or potentially harmful. The conclusion of atypicality, however, was a result of studying the constitutional discipline of broadcasting and telecommunications activities, which had undergone profound changes with the advent of Constitutional Amendment 08/1995. Despite this, more than ten years after that study and more than fifteen years after the constitutional reform of telecommunications, there is still an immense contradiction between the constitutional order inaugurated in 1988 and reformed in 1995 and the state broadcasting policy which, while benefiting small groups with political or economic penetration in the country, represses the activity of local use of the electromagnetic spectrum, even to the detriment of containing serious crimes. Now is the time to discuss the scope of the criminal law on the use of the electromagnetic spectrum and, more than ever, the Judiciary is called upon to interpret the legislation on the subject in accordance with the constitutional provisions that underpin the Democratic Rule of Law and guarantee freedom of communication at all levels.
Keywords: broadcasting; telecommunications; criminalization; atypicality; Law No. 4.117/1962; Law No. 9.472/1997